RNA-Seq Profiling to Investigate the Mechanism of Qishen Granules on Regulating Mitochondrial Energy Metabolism of Heart Failure in Rats. (31st December 2021) - He, Hao; Li, Changxiang; Lu, Xiangyu; Li, Yanqin; Li, Xuan; Sun, Xiaoqian; Tang, Binghua; Wu, Yan; Li, Chun
Abstract : Background . Qishen granules (QSG) are a frequently prescribed formula with cardioprotective properties prescribed to HF for many years. RNA-seq profiling revealed that regulation on cardiac mitochondrial energy metabolism is the main therapeutic effect. However, the underlying mechanism is still unknown. In this study, we explored the effects of QSG on regulating mitochondrial energy metabolism and oxidative stress through the PGC-1 α /NRF1/TFAM signaling pathway. RNA-seq technology revealed that QSG significantly changed the differential gene expression of mitochondrial dysfunction in myocardial ischemic tissue. The mechanism was verified through the left anterior descending artery- (LAD-) induced HF rat model and oxygen glucose deprivation/recovery- (OGD/R-) established H9C2 induction model both in vivo and in vitro . Echocardiography and HE staining showed that QSG could effectively improve the cardiac function of rats with myocardial infarction in functionality and structure. Furthermore, transcriptomics revealed QSG could significantly regulate mitochondrial dysfunction-related proteins at the transcriptome level. The results of electron microscopy and immunofluorescence proved that the mitochondrial morphology, mitochondrial membrane structural integrity, and myocardial oxidative stress damage can be effectively improved after QSG treatment. Mechanism studies showed that QSG increased the expression level of mitochondrial biogenesis factor PGC-1 α /NRF1/TFAM protein and regulated the balance of mitochondrial fusion/fission protein expression. QSG could regulate mitochondrial dysfunction in ischemia heart tissue to protect cardiac function and structure in HF rats. The likely mechanism is the adjustment of PGC-1 α /NRF1/TFAM pathway to alleviate oxidative stress in myocardial cells. Therefore, PGC-1 α may be a potential therapeutic target for improving mitochondrial dysfunction in HF.